Saturday

April 19, 2014

April 19, 2014

Posted by **Mallory** on Sunday, March 11, 2007 at 5:16pm.

|2x - 3|^2 - 6|2x - 3| + 5=0

I know you are goood with this stuff

Math question here.

let |2x - 3| = y then you have

y^2 - 6y + 5 = 0

(y-5)(y-1)=0

y = 5 or y = 1

or |2x - 3| = 5 or |2x - 3| = 1

So you have |2x - 3| = 5

giving you:

2x - 3 = 5 or -2x + 3 = 5

2x= 4 -2x = 2

x = 2 x = -1

repeat the same steps with |2x - 3| = 1 for 2 more answers.

**Related Questions**

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

Math - Prove each identity: a) 1-cos^2x=tan^2xcos^2x b) cos^2x + 2sin^2x-1 = sin...

Math33333 - Please help me! Problem: x+2 x-3 _________ - _________ 2x^2+5x+2 2x^...

College Algebra - Here is the whole question... I have figured most of it out ...

Algebra - Need help with this problem, 2x+y=6 solve for y 2x+y=6 subtract 2x ...

math - if x is not equal to negative 3/2, (2x^3-x^2-6x)/(2x+3)equals? a. x-2 b. ...

math - Simplify sin^2x+cos^2x+sec^2x -tan^2x+csc^2x-cot^2x

math - translate and simplify"six less than twice the sum of a number and three...

math - I asked this question before and I was told my work was correct by my ...

math - Which equation demonstrates the commutative property of addition? a. 2x+y...